1979
DOI: 10.1126/science.225798
|View full text |Cite
|
Sign up to set email alerts
|

Calmodulin Activation of Adenylate Cyclase in Pancreatic Islets

Abstract: Pancreatic islets contain calmodulin. The protein binds to a particulate fraction derived from the islets and stimulates adenylate cyclase activity in this subcellular fraction, both phenomena being activated by ionized calcium. A calcium-dependent stimulation of adenylate cyclase by endogenous calmodulin may contribute to the accumulation of adenosine 3',5'-monophosphate evoked by insulin releasing agents in the islet cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
87
2
3

Year Published

1980
1980
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 236 publications
(99 citation statements)
references
References 26 publications
7
87
2
3
Order By: Relevance
“…This protein has recently been identified in rat islets [30,31], and the calmodulin inhibitor trifluoperazine [32] found to inhibit insulin secretion [30]. A similar Induced insulin release was also inhibited by vinblastine and colchicine.…”
Section: Discussionmentioning
confidence: 97%
“…This protein has recently been identified in rat islets [30,31], and the calmodulin inhibitor trifluoperazine [32] found to inhibit insulin secretion [30]. A similar Induced insulin release was also inhibited by vinblastine and colchicine.…”
Section: Discussionmentioning
confidence: 97%
“…Previous work on whole islets emphasised the importance of calcium for islet adenylyl cyclase activity. Two studies [47,48] have shown that homogenates of rat isolated islets contain Ca 2+ -calmodulin-dependent AC activity. We show that the Ca 2+ -calmodulin effects interact synergistically with that of G sα .…”
Section: Discussionmentioning
confidence: 99%
“…cAMP is formed by adenylyl cyclases in response to G s -coupled receptor agonists, such as glucagon, the incretin hormones glucagon-like peptide-1 (GLP-1) and gastric inhibitory popypeptide (GIP), as well as the neuropeptides pitutitary adenylate cyclase activating polypeptide (PACAP) and vasoactive intestinal popypeptide (VIP). Also glucose-stimulated islets show a modest elevation of cAMP (Charles et al, 1973;Grill and Cerasi, 1973;Hellman et al, 1974;Sharp, 1979), an effect that has been attributed to the elevation of [Ca 2+ ] i (Charles et al, 1975;Valverde et al, 1979). From the observation that purified β-cells, lacking influence from the glucagon-producing α-cells, show reduced cAMP content and impaired secretory capacity, it was suggested that cAMP has a permissive role in glucose-induced insulin release and that the effect of the sugar on cAMP content represents amplification of glucagon-induced cAMP production (Schuit and Pipeleers, 1985).…”
Section: Cyclic Ampmentioning
confidence: 99%